The Godfather in pictures an unofficial companion - Nourmand, Tony (Boxtree, 2007)
The Godfather Parts I,II, and III are among the best loved movies in the history of cinema. 'The Godfather in Pictures' collects covers, behind-the-scenes photographs and costume designs in one volume.